Medical Students’ Achievement in Elective Posting Using Online Platform Under Movement Control Order During COVID-19 Pandemic (Bangladesh Journal of Medical Science, 2025)
Background Medical schools worldwide emphasize elective posting (EP) in undergraduate medical curriculum, allowing students freedom to choose a project of their interest. At University Kebangsaan Malaysia (UKM), medical faculty, EP of four-weeks takes place at the end of year-3, where students freely choose project. Objectives During COVID -19 pandemic in 2020 under movement control order (MCO), there was a shift in the types of electives undertaken by students, along with shifting of teaching-learning from face-to-face to online. Method This study aimed to determine the students’ achievement during EP under MCO. It was a retrospective study designed and conducted from October 2020 to September 2021 by examining 122 year-3 medical students’ EP performance documents of 488 Padlet journals uploaded weekly to Padlet.com and 122 reflective reports submitted at completion of EP. A qualitative data analysis was done, and a panel of experts verified the outcomes. Appropriate sentences were coded into several themes and subthemes. Results Students’ achievement in EP was categorized into three major themes: Theme-1: Course Learning Outcomes (CLO) soft skills; Theme-2: Additional soft skills; and Theme-3: Hard skills. Reflective was the main subtheme under CLO soft skill, showing the students’ ability to reflect. Adaptability and problem-solving emerged as key skills under theme-2, while media production was noted key skills under theme-3. Despite the imposed restrictions during pandemic with shifting teaching-learning approach, students achieved the skills stated in the CLO of elective course, including additional soft and hard skills. Conclusion These findings can be utilized to boost the design and implementation of future elective postings.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 629-640